Removable singularities for p-harmonic maps: the subquadratic case - Gastel, Andreas; Grotowski, Joseph Francis; Kronz, Manfred (Advances in Geometry, 2005)
We prove a removable singularity theorem for p -harmonic maps in the subquadratic case. The theorem states that an isolated singularity of a weakly p -harmonic map is removable if the energy is sufficiently small in a neighbourhood of the singularity. © de Gruyter 2005.
UnivIS-Import:2015-03-09:Pub.2005.nat.dma.lma2.remova